The Interplay of Mindfulness, Impulsive Buying, and Perceived Risk in Buy Now Pay Later (BNPL) Usage among Mature Generations in Indonesia - Isnaini Nuzula Agustin; Nurika Rama Nasya; Candy (Journal of Consumer Sciences, 2025)
Background: Concerns are being raised about the effects of the growing use of Buy Now Pay Later (BNPL) in Indonesia on financial well-being and consumer behavior, particularly among Millennials and Gen X. Purpose: This study aims to examine the relationship between BNPL usage and financial well-being, considering the role of mindfulness and the tendency for impulsive buying. It further explored the role of Perceived Risk as a moderator in the relationship between mindfulness and BNPL usage. Method: This study employed a quantitative, scientific method using numerical data and analyzed using statistical methods. The sampling method used was purposive, specifically targeting BNPL users from the Gen X and Millennial demographics in Indonesia. Data collection using a questionnaire yielded 327 respondents. Findings: Mindfulness was positively correlated with BNPL usage, reducing the tendency for impulsive buying. Conversely, the tendency to make impulsive purchases increased BNPL usage. Perceived Risk further moderated the relationship between mindfulness and planned BNPL usage. Conclusions: Mindful adult users were more inclined to avoid impulsive buying and instead used BNPL for more necessary expenses, indicating a nuanced relationship between psychological traits and financial behavior. Research implication: These results helped policymakers develop initiatives to enhance financial education and reduce the risks associated with BNPL adoption.